2003
DOI: 10.1002/ajmg.a.20377
|View full text |Cite
|
Sign up to set email alerts
|

New syndrome: Focal dermal hypoplasia, morning glory anomaly, and polymicrogyria

Abstract: Regional skin hypoplasia has been described in several genetic syndromes, including focal dermal hypoplasia (FDH), microphthalmia with linear skin defects (MLS), oculocerebrocutaneous syndrome (OCCS), and terminal osseous dysplasia and pigmentary defects (TODP). All but OCCS have been reported to follow an X-linked inheritance pattern. We describe a 14-year-old girl with clinical features overlapping with these disorders. She had mild mental retardation, macrocephaly, microphthalmia, right-sided morning glory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The features seen in this patient, particularly the localization to the right side of the face and chest, together with grey matter heterotopias, are similar to the case reported by Giampietro et al, (2004), although without any retinal or hand involvement. The absence of digital abnormalities together with the brain abnormalities suggest a diagnosis other than focal dermal hypoplasia (Temple et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…The features seen in this patient, particularly the localization to the right side of the face and chest, together with grey matter heterotopias, are similar to the case reported by Giampietro et al, (2004), although without any retinal or hand involvement. The absence of digital abnormalities together with the brain abnormalities suggest a diagnosis other than focal dermal hypoplasia (Temple et al, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…21,28 Abnormalities of the visual pathways have also been reported in MGDA, including atrophy/hypoplasia of the contralateral optic chiasm as well as optic nerve glioma. 3,29 In our cohort, we observed each of these findings in 1 patient. The optic chiasm atrophy/hypoplasia in MGDA could result either from retrograde axonal degeneration in the setting of an intracranial lesion or from antegrade degeneration related to the ganglion cell deficit within the developing retina.…”
Section: Figmentioning
confidence: 61%
“…Twelve cases, a significant proportion of the original 40, were excluded. Among the 12 was the report by Giampietro et al [2004], in which the authors considered but then rejected a diagnosis of OCCS; the patients described by Braun‐Vallon et al [1958], and by Leichtman et al [1994], in which the diagnosis of OCCS was suggested by subsequent authors.…”
Section: Discussionmentioning
confidence: 99%